Comparative chloroplast genomics of Caryophyllaceae species: insights into sequence variations and phylogenetic evolution - Lucun Yang; Yongqing Zhu; Qing Hua (BMC Plant Biology)
Abstract Background Caryophyllaceae contains 100 genera and 3000 species, many of which are valuable both ecologically and economically. However, as past research has shown, the fundamental phylogenetic relationships of Caryophyllaceae are still debatable, and molecular dating based on chloroplast genomes has not been thoroughly examined for the entire family. Methods In this study, the complete chloroplast genome sequences of Arenaria kansuensis Maxim., A. roborowskii Maxim., A. przewalskii Maxim., and Silene aprica Turcz were described. Additionally, the four newly generated along with eighteen published chloroplast genomes of Caryophyllaceae were included for comparative genomics analysis. Results These 22 chloroplast genomes had typical quadripartite structure, with 128–134 distinct genes and lengths ranging from 133,621 bp to 153,957 bp. The 22 Caryophyllaceae chloroplast genomes showed significant variations in the number of long repeats and SSR types; mononucleotide repeats (A/T) and palindromic repeats were the most common types. Three substantially divergent areas containing atpB-rbcL, rbcL-accD, and accD were found by further comparative study, which could serve as effective molecular markers. The codon bias of chloroplast genomes in Caryophyllaceae were mainly affected by natural selection, but other factors such as mutation pressure could also affect the codon bias to some extent. Fourteen optimal codons were identified in the chloroplast genome of Caryophyllaceae. Phylogenetic analysis demonstrated that the monophyly of any of the three recognized subfamilies within Caryophyllaceae was not supported by our data. Meanwhile, seven well-supported clades correspond to 8 tribes were found in phylogenetic trees. The results of molecular dating demonstrated that the divergence between Caryophyllaceae and Amaranthaceae was estimated to occur in 69 Ma. The Paronychieae was the oldest tribe of the eight tribes included in this study, diverged at 59.92 Ma. Conclusion This study provides resources for further investigations on the identification, genetic engineering, evolution, and phylogeny of Caryophyllaceae species.